Characterization of a second proliferating cell nuclear antigen (PCNA2) from Drosophila melanogaster. - Ruike, T.; Takeuchi, R.; Takata, K.; Oshige, M.; Kasai, N.; Shimanouchi, K.; Kanai, Y.; Nakamura, R.; Sugawara, F.; Sakaguchi, K. (FEBS Journal, 2006)
The eukaryotic DNA polymerase processivity factor, proliferating cell nuclear antigen, is an essential component in the DNA replication and repair machinery. In Drosophila melanogaster, we cloned a second PCNA cDNA that differs from that encoded by the gene mus209 (for convenience called DmPCNA1 in this article). The second PCNA cDNA (DmPCNA2) encoded a 255 amino acid protein with 51.7% identity to DmPCNA1, and was ubiquitously expressed during Drosophila development. DmPCNA2 was localized in nuclei as a homotrimeric complex and associated with Drosophila DNA polymerase delta and epsilonin vivo. Treatment of cells with methyl methanesulfonate or hydrogen peroxide increased the amount of both DmPCNA2 and DmPCNA1 associating with chromatin, whereas exposure to UV light increased the level of association of only DmPCNA1. Our observations suggest that DmPCNA2 may function as an independent sliding clamp of DmPCNA1 when DNA repair occurs.